Using wireless and mobile technologies to enhance teaching and learning strategies - Kahkashan Tabassum (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The tremendous development and sensational popularity  of smart mobile devices that offer remarkable availability of seamless  and uninterrupted  communication services at anytime, anywhere,  to any content as well as any prospects represent a new cohort of technological tools that could be utilized for inculcating creative skills in young children. Now a days many companies are  manufacturing lot of apps that target children education and entertainment. Both the Parents and educators find a huge responsibility in evaluating and  selecting such devices and decide which of these offer potential educational benefits for their children. This decision is critical to them since they  restricted tools to evaluate the applications available in the market. Hence the development of an  interactive and multisensory component based mobile application environment with integrated physical and virtual reality scenario could solve the issue related to the children education and entertainment. This is not just  limited to education and the entertainment domain but will explore essential features of virtual reality environment and interactivity. Children with special education needs find it difficult to understand  new knowledge and concept but by the use of virtual reality worlds produced for children could enhance their level of understanding. Therefore this paper dscusses the development of  adaptable, customizable and virtual reality based compliant applications for children. These applications would be useful to enhance learning essentials and improve  diverse sensory and cognitive impairments in even children with special needs by resolving  mobility issues. This application could be made available on i-pads, tablets, etc  and will be intelligent to perform switch between the different intellectual ranges of children accessing it. In other words it will present self-adaptability feature. This research study also focuses on the activities that are suitable for learning purposes with students with impairments.